Modeling economic-environmental decision making for agricultural land use in Argentinean Pampas - Cabrini, Silvina María; Calcaterra, Carlos Pablo (2018)
This research evaluates the economic and environmental impacts of land allocation to crops and extensive livestock production in the Argentine Pampas using compromise programming. Two economic indicators (gross margin, direct costs) and five environmental indicators (organic carbon input to soil, nutrient balances, agrochemicals impact and soil erosion) are considered. The tradeoff between economic and environmental objectives is assessed and the preferred land allocation schemes determined by the multicriteria model are compared to the current land use in the region of Pergamino, North of Buenos Aires, Argentina. Results indicate that it is important to consider not only the environmental-economic tradeoff in farming, but also the conflict across different environmental criteria in order to determine whether it is reasonable to stimulate activities which improve some environmental indicators at the expense of getting less desirable values in others. For instance, an increase of productivity in agriculture enhances soil organic carbon content but it may increase the risk of contamination with agrochemicals and nutrients. Results are consistent with the notion that extensive crop-livestock production systems are more balanced than continuous crop farming. According to model results, optimal land assignment is a combination of crop and livestock activities (62 and 38% of land, respectively) which is associated with lower agrochemical use, greater organic carbon input to soil, better soil protection from erosion and more efficient nutrient cycling. This land assignment presents a decrease of 20% in the economic gross margin compared to the continuous agriculture scheme that maximizes the economic result. The comparison between current land use and the optimal land assignment based on model results show that farmers assign a smaller fraction of land to extensive livestock production (2–4%), than in the most balanced compromise solution (38%). Results also suggest that it would be appropriate to encourage farmers to reduce the area of land assigned to full-season soybeans.